Contamination of smoked fish and smoked-dried fish with polycyclic aromatic hydrocarbons and biogenic amines and risk assessment for the Beninese consumers. (August 2021) - Iko Afé, Ogouyôm Herbert; Saegerman, Claude; Kpoclou, Yénoukounmè Euloge; Douny, Caroline; Igout, Ahmed; Mahillon, Jacques; Anihouvi, Victor Bienvenu; Hounhouigan, Djidjoho Joseph; Scippo, Marie-Louise
Abstract: The present study aims to assess the contamination of smoked and smoked-dried fish sampled on Beninese market with biogenic amines and polycyclic aromatic hydrocarbons (PAHs). Fifteen PAHs, ten biogenic amines and nineteen amino acids were analysed in thirty-six fish samples, using liquid chromatography techniques. The assessment of consumer exposure was carried out by calculating the estimated daily intake (EDI) which was compared to a toxicological reference value. The exposure to histamine, the most toxic biogenic amine, was calculated and compared with an acute reference dose (ARfD) of 50 mg/meal. The margin of exposure (MOE) to PAHs was calculated as the ratio between benchmark PAH levels and EDI. MOE to carcinogenic compounds below 10, 000 indicates a potential concern for human health. Amino-acid profile varied as a function of fish species with a high content of histidine (the precursor of histamine) recorded in Cypselurus cyanopterus, the Atlantic flying fish (2.9 g/100 g, dry weight) followed by Scomber scombrus, the Atlantic mackerel (1.9 g/100 g, dry weight). High histamine concentration (4, 384.2 mg/kg) was recorded in one sample of C. cyanopterus, a non-scombroid fish, exceeding 44 times the maximal limit of 100 mg/kg, set by the EU and Benin regulations. Histamine intake calculated using the maximum measured histamine concentration exceeded the ARfD. Concerning the PAH contamination, none of the smoked and smoked-dried fish samples were compliant with the EU regulation, and the MOE of the consumers were below 10, 000 (for both median and maximum PAH contamination levels). In conclusion, the consumption of smoked and smoked-dried fish could represent a major concern for the Beninese consumer health because of both histamine and PAHs contamination. Highlights: A non-scombroid fish displays high histamine concentration of 4400 mg/kg. Histamine intake could exceed twenty-four times the acute dose of 50 mg/meal. Smoked fish sampled from Beninese markets are highly contaminated with PAH. Consumers of smoked fish are at risk of histamine intoxication and PAH induced cancer.